Surface Electromagnetic Waves at a Single Interface of Superconductor and Left-Handed Materials - Shabat, Mohammed M.; Hamada, M. S.; Sbaih, M. A. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The wave propagation characteristics along the single interface of superconductor and left-handed materials are investigated theoretically. An expression for the complex permittivity of a superconductor is derived in the approximation of two-component plasma containing "normal" and "superconducting" electrons. Basic relations are obtained in the general case at temperatures T â‰¤ Tc where c T is the critical temperature. The frequency, the structure, and the temperature dependences of surface electromagnetic waves propagating along a single interface of a superconductor-left-handed material interface are computed, analyzed and discussed.